2012
DOI: 10.1378/chest.11-3199
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Perspectives of Surrogate Decision-Makers Regarding Critical Illness Research

Abstract: Objective : We undertook the current investigation to explore how the pressures of serving as a surrogate decision-maker (SDM) for an acutely ill family member infl uence attitudes regarding clinical investigation. Methods: We conducted a prospective study involving SDMs for critically ill patients cared for in the ICUs of two urban hospitals. Measurements included participation in focus groups designed to explore perceptions of ICU care and clinical research. Audiotapes were transcribed and analyzed to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…We also found that while RCs' impressions of SDMs rationale for providing consent were similar to those expressed by SDMs, their impressions of why SDMs declined consent were qualitatively different with research personnel highlighting that SDMs were overwhelmed [8/32 (25.0 %)] and did not want to change current treatment [7/32 (21.9 %)]. In hypothetical scenarios, escalating study risk was associated with decreased SDM comfort in providing consent [5,19,20]. While underpowered, we did not find differences in consent rates between strategies or based on investigator or SDM-assigned study risk.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We also found that while RCs' impressions of SDMs rationale for providing consent were similar to those expressed by SDMs, their impressions of why SDMs declined consent were qualitatively different with research personnel highlighting that SDMs were overwhelmed [8/32 (25.0 %)] and did not want to change current treatment [7/32 (21.9 %)]. In hypothetical scenarios, escalating study risk was associated with decreased SDM comfort in providing consent [5,19,20]. While underpowered, we did not find differences in consent rates between strategies or based on investigator or SDM-assigned study risk.…”
Section: Discussionmentioning
confidence: 51%
“…Instead, SDMs valued the personal attributes of kindness, compassion, consideration, and professionalism in the person approaching them over their professional designation. Similar to others, our SDMs expressed a need to appraise the risks and benefits of participation, the potential for participation to benefit the patient or others, and their trust in the health care team [18,20,26]. Additionally, they valued being approached privately and in-person, when not in crisis, and having time to contemplate their decisions and to reflect on personal and patient values regarding research participation.…”
Section: Discussionmentioning
confidence: 66%
“…Because critically ill patients frequently lack decision-making capacity, consent and participation in research often falls to patients’ families 1–5 Sending surveys to family members after the death of a patient is a common method for collecting data regarding the quality of palliative care. A previous study demonstrated systematic differences between patients whose family members completed surveys after a patient’s death in the ICU and those who did not.…”
Section: Contextmentioning
confidence: 99%
“…35 Participants were recruited from the surgical and medical ICUs of two tertiary-care institutions (Barnes Jewish Hospital (BJH), St. Louis, MO and Parkland Hospital (PH), Dallas, TX). These study sites were chosen because of their demographic and ethnic diversity.…”
Section: Sdm Sample and Recruitmentmentioning
confidence: 99%